Flourishing and academic engagement among adolescents with overweight and obesity - Rupp, Kristie; McCoy, Stephanie M. (International Journal of Adolescent Medicine and Health, 2018)
Abstract Background Overweight and obesity in adolescence are associated with several negative health indicators; the association with flourishing, an indicator of overall well-being, is less clear. Objectives To examine associations between weight status and indicators of flourishing and academic engagement in adolescents. Subjects Analyses included 22,078 adolescents (10–17 years) from the 2016 National Survey of Children’s Health. Methods Adolescents were grouped according to body mass index (BMI) classification; outcomes included indicators of flourishing and academic engagement. Logistic regression models assessed the odds of each outcome comparing adolescents with overweight and adolescents with obesity to healthy weight adolescents. Results For flourishing, adolescents with overweight and adolescents with obesity were less likely to stay calm during a challenge (17% and 30%, respectively; p < 0.01); adolescents with obesity were 30% less likely to finish a task they started (p < 0.001), and 34% less likely to show interest in new things (p < 0.001) in comparison to healthy weight peers. Adolescents with obesity were 26% less likely to care about doing well in school (p < 0.001), and adolescents with overweight and adolescents with obesity were significantly less likely to complete all required homework (19% and 34%, respectively) (p < 0.001), in comparison to healthy weight peers. Conclusions A comprehensive approach to addressing overweight and obesity in adolescence should target improving academic engagement and flourishing to promote overall well-being.
3 citations (Crossref) [2023-10-31]
Keywords: academics; adolescence; dept.hms; dept.pch; flourishing; obesity; peer-reviewed

Bullying perpetration and victimization among adolescents with overweight and obesity in a nationally representative sample - Rupp, Kristie; McCoy, Stephanie M. (Childhood Obesity, 2019)
19 citations (Crossref) [2023-10-31]
Keywords: dept.hms; peer-reviewed

Reducing sedentary behavior versus increasing moderate-to-vigorous intensity physical activity in older adults: a 12-week randomized, clinical trial - Gibbs, Bethany Barone; Brach, Jennifer S.; Byard, Tom; Creasy, Seth; Davis, Kelliann K.; McCoy, Stephanie; Peluso, Anna; Rogers, Renee J.; Rupp, Kristie; Jakicic, John M. (Journal of Aging and Health, 2016)
Objective: To compare the effects of behavioral interventions targeting decreased sedentary behavior versus increased moderate-to-vigorous intensity physical ac...
45 citations (Crossref) [2023-10-31] Publisher: SAGE PublicationsSage CA: Los Angeles, CA
Keywords: dept.hms